2014
DOI: 10.1055/s-0033-1340849
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrogenation of Low-Reactivity Carbonyl Groups Using Bifunc­tional Chiral Tridentate Ligands

Abstract: This account describes studies on the catalytic hydrogenation of carbonyl groups that are not readily reduced. The development of well-defined chiral phosphine-diamine ruthenium catalysts for hydrogenation of ketones and esters is described. These chiral catalysts promote the hydrogenation of ketones functionalised with tertiary alkyl and gem-dimethyl groups with enantioselectivities of up to 98% ee. They also reduce a range of heterocyclic and nitrilefunctionalised ketones that react slowly with or inhibit ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…[20] These catalysts displayed unusual reactivity and high enantioselectivity in the hydrogenation of low-reactivity bulky ketones. [21] A wide range of less reactive bulky ketones 1, including some problematic substrates such as bulky heterocyclic ketones, can be reduced to give the corresponding chiral alcohols 2 with moderate to good enantioselectivities (up to 94% ee) (Scheme 3). Changing from ruthenium to iridium, Clarke [22] et al demonstrated the hydrogenation of ketones 1 bearing an aryl substituent and a secondary alkyl group with an iridium-P,N,N-ligand L1 catalyst, which showed higher reactivity and selectivity than that obtained with a ruthenium catalyst derived from the same ligand (Scheme 4).…”
Section: Asymmetric Hydrogenation Of C=o Bonds 21 Asymmetric Hydrogen...mentioning
confidence: 99%
See 1 more Smart Citation
“…[20] These catalysts displayed unusual reactivity and high enantioselectivity in the hydrogenation of low-reactivity bulky ketones. [21] A wide range of less reactive bulky ketones 1, including some problematic substrates such as bulky heterocyclic ketones, can be reduced to give the corresponding chiral alcohols 2 with moderate to good enantioselectivities (up to 94% ee) (Scheme 3). Changing from ruthenium to iridium, Clarke [22] et al demonstrated the hydrogenation of ketones 1 bearing an aryl substituent and a secondary alkyl group with an iridium-P,N,N-ligand L1 catalyst, which showed higher reactivity and selectivity than that obtained with a ruthenium catalyst derived from the same ligand (Scheme 4).…”
Section: Asymmetric Hydrogenation Of C=o Bonds 21 Asymmetric Hydrogen...mentioning
confidence: 99%
“…The result showed that a secondary NH group rather than NH 2 plays an important role in achieving high reactivity [20] . These catalysts displayed unusual reactivity and high enantioselectivity in the hydrogenation of low‐reactivity bulky ketones [21] . A wide range of less reactive bulky ketones 1 , including some problematic substrates such as bulky heterocyclic ketones, can be reduced to give the corresponding chiral alcohols 2 with moderate to good enantioselectivities (up to 94% ee) (Scheme 3).…”
Section: Asymmetric Hydrogenation Of C=o Bondsmentioning
confidence: 99%
“…Although high enantioselectivity was achieved for acetophenone, only 15–20% yield was observed. Subsequently, PNN-L2 was developed by Clarke in 2007. A secondary NH rather than primary NH 2 played a significant role in achieving high reactivity . In 2018, PNN-L3 was developed and employed in the Mn-catalyzed ketone ATH reaction .…”
Section: Overview Of Chiral Tridentate Ligands For Hydrogenationmentioning
confidence: 99%
“…The catalytic reduction of esters to alcohols (Scheme ) is still an open challenge to industry and academia alike as the common available alternatives suffer from many disadvantages from the point of view of large‐scale synthesis 6062. For example, the stoichiometric reduction of esters requires large quantities of metal hydride reagents like LiAlH 4 that raises obvious environmental concern in case of the scale‐up applications 63.…”
Section: 6 Hydrogenation Of Estersmentioning
confidence: 99%
“…Quite interestingly, a dimeric ruthenium complex 44 exhibited an exceptionally high turnover number (TON) of 53,900 in 1 hour for the ethyl hexanoate hydrogenation reaction performed at 40 bar of H 2 pressure and 100 °C 68. The DMSO‐coordinated ruthenium complexes including a chiral complex 45 and the achiral complexes 46 – 48 successfully used for the asymmetric as well as achiral versions of the ester hydrogenation reactions 60,69. Using molecular hydrogen, the selective hydrogenation of α‐fluorinated esters were carried out with bifunctional pincer‐type ruthenium(II) catalysts 49 – 51 leading to fluorinated alcohols or fluoral hemiacetals 70.…”
Section: 6 Hydrogenation Of Estersmentioning
confidence: 99%